Pengembangan Media Pembelajaran Berbasis Nearpod Pada Mata Pelajaran Geografi Materi Dinamika Hidrosfer Kelas X IPS SMA Negeri 9 Gorontalo Utara - Putri Podu, Regina; Lihawa, Fitryane; Nurfaika, Nurfaika (-, 2025)
Development of Nearpod-Based Learning Media for Geography Subject on Hydrosphere Dynamics. This study aimed to develop Nearpod-based learning media for the geography subject of Hydrosphere Dynamics for the tenth-grade (X) Social Science students at SMA Negeri 9 Gorontalo Utara. The Nearpod learning media was developed using the ADDIE development model, which encompasses the following stages: analysis, design, development, implementation, and evaluation. Based on the study findings, the validation score from the product design expert was 86.6%, indicating a very valid level of validity. This was followed by content expert validation with a score of 85% categorized as very valid. The subject matter expert validation score was 90%, categorized as very valid category as well. Furthermore, the evaluation of student responses (on a limited scale) to the learning media resulted a score of  76,3%, while the general student response (on a broader scale) reached 87.4%. Therefore, the Nearpod learning media for the geography subject on Hydrosphere Dynamics at SMA Negeri 9 Gorontalo Utara categorized as being good or suitable for use. It can be concluded that the development of Nearpod learning media for the Hydrosphere Dynamics topic is appropriate for use in both online learning processes.